Methylcellulose Based Thermally Reversible Hydrogel System for Tissue Engineering Applications - Ram V. Devireddy; Sreedhar Thirumala; Jeffrey M. Gimble (Cells, 2013)
The thermoresponsive behavior of a Methylcellulose (MC) polymer was systematically investigated to determine its usability in constructing MC based hydrogel systems in cell sheet engineering applications. Solution-gel analyses were made to study the effects of polymer concentration, molecular weight and dissolved salts on the gelation of three commercially available MCs using differential scanning calorimeter and rheology. For investigation of the hydrogel stability and fluid uptake capacity, swelling and degradation experiments were performed with the hydrogel system exposed to cell culture solutions at incubation temperature for several days. From these experiments, the optimal composition of MC-water-salt that was able to produce stable hydrogels at or above 32 °C, was found to be 12% to 16% of MC (Mol. wt. of 15,000) in water with 0.5× PBS (~150mOsm). This stable hydrogel system was then evaluated for a week for its efficacy to support the adhesion and growth of specific cells in culture; in our case the stromal/stem cells derived from human adipose tissue derived stem cells (ASCs). The results indicated that the addition (evenly spread) of ~200 µL of 2 mg/mL bovine collagen type -I (pH adjusted to 7.5) over the MC hydrogel surface at 37 °C is required to improve the ASC adhesion and proliferation. Upon conﬂuence, a continuous monolayer ASC sheet was formed on the surface of the hydrogel system and an intact cell sheet with preserved cell–cell and cell–extracellular matrix was spontaneously and gradually detached when the grown cell sheet was removed from the incubator and exposed to room temperature (~30 °C) within minutes.